2004
DOI: 10.1096/fj.03-1065fje
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol accumulation in human obesity and type 2 diabetes is associated with increased rates of skeletal muscle fatty acid transport and increased sarcolemmal FAT/CD36

Abstract: We examined whether, in human obesity and type 2 diabetes, long chain fatty acid (LCFA) transport into skeletal muscle is upregulated and contributes to an excess intramuscular triacylglycerol accumulation. In giant sarcolemmal vesicles prepared from human skeletal muscle, LCFA transport rates were upregulated approximately 4-fold and were associated with an increased intramuscular triacylglycerol content in obese individuals and in type 2 diabetics. In these individuals, the increased sarcolemmal LCFA transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
339
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(370 citation statements)
references
References 62 publications
(111 reference statements)
23
339
7
1
Order By: Relevance
“…This is in accordance with another study showing that IMCL content in myotubes from lean control and obese non-diabetic participants was significantly related to BMI of the donor [5]. However, we and others [10] have shown that type 2 diabetes alone, in the absence of whole-body indicators of obesity, is also associated with skeletal muscle lipid accumulation. Our study provides evidence that this finding is limited to fresh skeletal muscle and is not observed in primary myotubes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in accordance with another study showing that IMCL content in myotubes from lean control and obese non-diabetic participants was significantly related to BMI of the donor [5]. However, we and others [10] have shown that type 2 diabetes alone, in the absence of whole-body indicators of obesity, is also associated with skeletal muscle lipid accumulation. Our study provides evidence that this finding is limited to fresh skeletal muscle and is not observed in primary myotubes.…”
Section: Discussionsupporting
confidence: 93%
“…Myotubes were incubated with antibody raised against desmin and visualised using a secondary antibody conjugated to Alexa 546 (red). Nuclei in cells were stained by DAPI (blue [28,29] and obese participants [10] compared with controls. In Fig.…”
Section: Non-t2dmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive PGC-1α production induces many undesirable consequences, including abnormal mitochondrial proliferation, disruption of myofibrillar architecture, displacement of nuclei [12], obesity, intramuscular lipid accumulation and insulin resistance [10,11]. We [3,13] have suggested that insulin resistance in PGC-1α transgenic mice [10,11] may stem from a large, PGC-1α-induced increase in the fatty acid transporter, fatty acid translocase (FAT), which has been associated with increases in intramuscular lipids and insulin resistance in humans and in animals [14,15]. Viewed in this light, PGC-1α-induced insulin resistance in transgenic mice is less of a paradox than has been suggested [11].…”
Section: Introductionmentioning
confidence: 99%